The impact of the ecological sustainability of landscapes on the formation of the hydro-ecological state in the upper part of the Prypiat River basin - Malovanyy, Myroslav; Boiaryn, Maria; Biedunkova , Olga; Voloshyn , Volodymyr; Netrobchuk , Iryna (Ecological Questions, 2025)
The relevance of this study is caused by the need to improve the methods of assessing the ecological sustainability of landscapes and their impact on the hydro-ecological state of river basins in the context of sustainable territorial development. The importance of the research is underscored in view of the increase in anthropogenic load on natural ecosystems, which requires new approaches to the assessment and forecasting of environmental changes. The purpose of the article is to study the interrelationships between the ecological sustainability of landscapes and the hydro-ecological state of water bodies using the example of the headwaters of the Prypiat River. The research used methods of mathematical modelling and statistical data processing to assess changes in the quality of surface water and the macrophyte index of rivers depending on the sustainability of landscapes by Spearman and Pearson correlation. The regions with a high coefficient of ecological sustainability of landscapes have better water quality indicators and a higher macrophyte index, which indicates a lower anthropogenic impact and a better hydro-ecological condition. The calculated Spearman rank correlation coefficients reveal the strong nature and probability of the relationship of independent variables (r=0.750–0.833). Pearson’s rank correlation coefficients described the connection from medium (r=0.454) to strong (r=0.870). Both direct and inverse linear dependencies between indicators were found.